Graphene growth controlled by the position and number of layers (n = 0, 1, and more than 2) using Ni and MgO patterned ultra-flat Cu foil. Issue 82 (10th November 2017) - Lee, Aram; Choi, Kyoung Soon; Park, Jinheon; Kim, Tae Soo; Lee, Jouhahn; Choi, Jae-Young; Yu, Hak Ki
Abstract : We have successfully controlled the number of graphene layers ( n -layer) by using a Cu–Ni–MgO hetero catalyst having a different catalytic activity and carbon solubility. Abstract : The catalytic activity of transition metals with regard to carbo-hydroxyl molecules (C x H y ) has triggered new technological developments in graphene growth. Both the opening of the Dirac-point by controlling the number of graphene layers as well as the patterning of the graphene are critical for applications such as transistor-based electronics. In this work, we have developed a method to control the position and number of layers ( n = 0, 1, and more than 2) during graphene growth based on our previous key ideas. This was achieved by using pre-patterned (Ni pre-patterned for more than 2 layers due to its high carbon solubility compared to Cu and MgO pre-patterned for 0 layer graphene due to the low catalytic activity and carbon solubility) ultra-flat Cu foils made using the peeled off method from a c-plane sapphire substrate.